2021
DOI: 10.3389/fsufs.2020.614349
|View full text |Cite
|
Sign up to set email alerts
|

Field Application of Organic Fertilizers Triggers N2O Emissions From the Soil N Pool as Indicated by 15N-Labeled Digestates

Abstract: Anaerobic digestion (AD) can generate biogas while simultaneously producing digestate which can be used as fertilizer. Feedstocks used for AD influence digestate composition, which in turn may affect carbon (C) and nitrogen (N) turn-over in soils and subsequently influence nitrous oxide (N2O) emissions after soil application. Assessment of greenhouse gas emissions from digestates can help to evaluate the overall sustainability of an agricultural production system. The objective of this study was therefore to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
4
4
0
Order By: Relevance
“…Consequently, it can be concluded that, in the case of dried solid, the addition of easily degradable C in combination with soil-derived NO 3 − triggered the N 2 O production and release. This notion is consistent with previous findings, based on experiments with 15 N-labeled manures [40,47,57,58]. It highlights the complexity of the presented issue and the importance of additional determination of the responsible N source.…”
Section: Further Processing Of Separated Solidsupporting
confidence: 92%
See 3 more Smart Citations
“…Consequently, it can be concluded that, in the case of dried solid, the addition of easily degradable C in combination with soil-derived NO 3 − triggered the N 2 O production and release. This notion is consistent with previous findings, based on experiments with 15 N-labeled manures [40,47,57,58]. It highlights the complexity of the presented issue and the importance of additional determination of the responsible N source.…”
Section: Further Processing Of Separated Solidsupporting
confidence: 92%
“…Increasing fluxes after fertilizer application and in connection with soil wetting (i.e., rainfall) (Figure 1) have already been reported in literature [22,[36][37][38][39]. In accordance with Hayakawa et al [22] and Häfner et al [40], the highest N 2 O peaks were observed within the first rainfall event (week 1). Hayakawa et al [22] assumed denitrifying activity as the main driver, since they measured a simultaneous increase in CO 2 release.…”
Section: General Factors Influencing the N 2 O Releasesupporting
confidence: 87%
See 2 more Smart Citations
“…However, a good proportion of nutrients such as N, phosphorous (P), and potassium (K) are retained [ 8 ]. The mineral contents and characteristics of digestate depend, most of the time, on the characteristics of the substrate and the modality of digestion [ 9 ]. These defined attributes, such as organic matter content, NH 4 , the C/N ratio, and N content present in the different substrates or feedstocks that form the digestates, will show differences in efficiencies and productivity in plants and soils, therefore making it the main source of this research.…”
Section: Introductionmentioning
confidence: 99%